2003
DOI: 10.1002/mc.10138
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of estrogen receptor alpha in prostate cancer

Abstract: Estrogen receptor (ER) alpha polymorphisms have been shown to be involved in the oncogenesis of several organs. We hypothesize that polymorphisms of the ERalpha gene are risk factors for prostate cancer. The genotypic distributions of six different loci (codons: 10 T-->C, 87 G-->C, 243 C-->T, 325 C-->G, 594 G-->A, and intron 1 C-->T) of the ERalpha gene were analyzed in prostate cancer tissues. The DNA from 115 cases of prostate cancer (Japanese population) was analyzed by sequence-specific polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 42 publications
(54 reference statements)
2
34
0
2
Order By: Relevance
“…The S10S polymorphism has been associated with a protective effect for other cancers such as endometrial cancer 17 and with increased risk for prostate and renal-cell carcinoma. 18,19 Based on these earlier studies and the confirmation in the present study, it seems plausible that the S10S variant or some other either in proximity, or in linkage disequilibrium with it, contributes to a decrease in breast cancer risk.…”
Section: Genotype Distributionsupporting
confidence: 79%
“…The S10S polymorphism has been associated with a protective effect for other cancers such as endometrial cancer 17 and with increased risk for prostate and renal-cell carcinoma. 18,19 Based on these earlier studies and the confirmation in the present study, it seems plausible that the S10S variant or some other either in proximity, or in linkage disequilibrium with it, contributes to a decrease in breast cancer risk.…”
Section: Genotype Distributionsupporting
confidence: 79%
“…The effects of these alleles can be expressed as relative odds associated with replacing one ESR1 (TA) 14 allele with one ESR1 (TA) 24 allele (odds ratio, 1.42; 95% confidence interval, 1.00-2.00; P = 0.05) or replacing one ESR1 (TA) 14 allele with one ESR1 (TA) 25 allele (odds ratio, 2.10; 95% confidence interval, 1.15-3.84; P = 0.02; Figs. 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study has found an association between a polymorphism in codon 10 of ESR1 and prostate cancer risk (24). Another recent study detected an effect of a different ESR1 SNP (rs2234693) on prostate cancer grade at diagnosis, but not total risk of either familial or sporadic prostate cancer (25), and no association with one ERh SNP.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ERα expression has been observed in some prostate cancer cell lines [86] as well as in hormone refractory and metastatic lesions suggesting its re-emergence as cancer progresses [87] although this has not been consistently seen in all studies [88]. It is also noteworthy that prostate cancer risk has been associated with genetic polymorphisms in the ERα gene particularly within Japanese and African American populations implicating a potential causal relationship between ERα mediated estrogenic action and prostate cancer [89,90].…”
Section: Erαmentioning
confidence: 99%